Dual cryoprotective strategies for ice-binding and stabilizing of frozen seafood: A review. (May 2021) - Zhu, Shichen; Yu, Jiehang; Chen, Xu; Zhang, Qi; Cai, Xixi; Ding, Yuting; Zhou, Xuxia; Wang, Shaoyun
Abstract: Background: Freezing-induced damages on seafood are pervasive problems that result from physical and biochemical changes during the freezing process. The formation of ice crystals is the main indirect trigger of these changes, including oxidation and aggregation of proteins, and lipid oxidation. The increasing concerns over the safety and low efficiency of traditional cryoprotectants (sucrose, polyols and phosphates) require the development of novel and healthy alternatives with high cryoprotective ability. However, the present cryoprotectants with ice-binding or stabilizing functions alone may not achieve the desired cryoprotection of frozen seafood. Hence, cryoprotectants with dual functions (ice-binding and stabilizing ability) have been proposed for frozen seafood, and have shown great potential to achieve the desired cryoprotection levels. Scope and approach: Here, we review the physical and biochemical changes induced by freezing, which contributes to the development of cryoprotective strategies for specific target. Aiming at spur development of ideal cryoprotectants that combine ice-binding ability and component stabilizing properties, we comprehensively discuss the structural basis of the present cryoprotectants, including ice-binding proteins, antifreeze peptides, polyphenols, nanomaterials, and factors influencing their activity. Key findings and conclusions: This review comprehensively outlines considerations for achieving ideal cryopreservation of frozen seafoods by combining ice-binding and stabilizing functions in cryoprotectants. Polysaccharides and nanomaterials are potential candidates for developing ideal cryoprotectants. However, further research is needed to optimize material selection and design hence improve cryoprotection performance. Graphical abstract: The development of cryoprotectants with dual strategies for antifreeze and stabilizing. Image 1 Highlights: The physical and biochemical changes induced by freezing treatments are reviewed. The mechanisms and impacting factors of the present cryoprotectants are emphasized. Dual cryoprotective strategies for antifreeze and stabilizing are proposed.